On the use of a test to exhaustion specific to tennis (TEST) with ball hitting by elite players - Brechbuhl, C.; Girard, O.; Millet, G. P.; Schmitt, L. (PLOS ONE, 2016)
Purpose: We aimed to a) introduce a new Test to Exhaustion Specific to Tennis (TEST) and compare performance (test duration) and physiological responses to those obtained during the 20-m multistage shuttle test (MSST), and b) determine to which extent those variables correlate with performance level (tennis competitive ranking) for both test procedures.